Feedlot performance and carcass traits of serially slaughtered finishing heifers - R.L. Hale; G.L. Bishop; J.R. Brethour; T.T. Marston (Kansas Agricultural Experiment Station Research Reports, 2004)
Two experiments were conducted at the KSU Agricultural Research Southeast Agricultural Research Center Center, Hays, Kansas, to measure feedlot gain and carcass traits of serially slaughtered, yearling crossbred heifers. In Exp. 1, 159 heifers averaging 792 lbs were randomly assigned to one of four slaughter groups, and slaughtered at 21-day intervals beginning at 92 days on feed. In Exp. 2, 181 heifers averaging 759 lbs were randomly assigned to one of four slaughter groups, and slaughtered at intervals of 19, 23 and 21 day, respectively, starting at 127 days. In both experiments, final weight, gain, and carcass weight increased with days on feed. Heifers did not gain body weight between 134 and 155 days on feed in Exp. 1, but heifers continued to gain body weight through 190 days on feed in Exp. 2. Despite having a lighter starting weight, final body weights and hot carcass weights were greater for heifers in Exp. 2 than in Exp. 1 because they had more time on feed. Ribeye area increased with time, although the ratio of ribeye area to carcass weight decreased over time. Increases in backfat and kidney, pelvic, and heart fat suggest that carcass gain increases in fat content over time. Yield grade and marbling scores also increased with each successive slaughter group. Quality grade improved with more days on feed in Exp. 1. Carcass quality was, however, hampered by significantly increased carcass maturity in Exp. 2. Although it is not well defined, the greatest increase in carcass fat deposition seemed to occur between 92 and 113 days on feed in Exp. 1, whereas the increases in carcass fat seemed to increase continually between 127 and 188 days on feed in Exp. 2.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Feedlot performance; Carcass traits; Finishing heifers